A Student's Experience and View on College Teaching and Learning - Kristin Atkinson, BS (Park University, 2013)
Through my college experience and my reflection on The Scholarship of Teaching and Learning Reconsidered, I have come to recognize several ideas that have greatly impacted me, my views on learning, and my actual learning. My overall experience in college has been beneficial because of the teachers who approached teaching with a more conscious effort and taught me to approach learning and my role as learner in the same way. This essay highlights many of the aspects of the chapter, "Teachers and Learning," that have been beneficial for me throughout my educational career, and a few notes on changes that may have helped.